Homeowning Motivation in Malaysia - Walter Tan Teck Hong (Journal of Accounting, Business and Management (JABM), 2009)
The residential property industry, which had grown rapidly in the 1980s, however, encountered overhang problems recently. Overhang of residential units has been getting worse and therefore, precautionary measures must be taken by the housing developers before it leads to a property glut. In order to address property overhang in the country, housing developers must recognize the importance of orienting their activities to consider how and why households are motivated to home owning. Factor analysis of the 25 questions was used to support the grouping of these questions into a smaller number of factors. Factors were used as constructs of the motivation of homeownership. The results conclude that Malaysian householders are motivated to become homeowners because they expect home owning will improve the home environment in which a child lives, improve neighborhood stability through higher properties maintenance and improvement, and longer tenure, and improve social capital and local amenities investments in the neighborhood. The motivation of home owning is crucial to housing developers as they have to be cautious before undertaking any new project. Housing developers should know what the market really wants and plan their products to take cognizance of the changing lifestyles of Malaysians.